Secure-base Relationships as Drivers of Professional Identity Development in Dual-career Couples - Petriglieri, Jennifer Louise; Obodaru, Otilia (Administrative Science Quarterly, 2019)
Through a qualitative study of 50 dual-career couples, we examine how partners in such couples shape the development of each other’s professional identities and how they experience and interpret the relationship between those identities. We found that the extent to which and how partners shaped each other’s professional identities depended on the couple’s attachment structure, that is, whether one partner—or both—experienced the other as a secure base. Someone comes to regard another person as a secure base when he or she experiences the other as both dependably supportive and encouraging of his or her exploratory behavior. Couples who had a unidirectional secure-base structure experienced conflict between the development of their professional identities. The partner who received a secure base pursued ongoing professional identity development, while the partner who provided a secure base foreclosed it. Couples who had a bidirectional secure-base structure experienced mutual enhancement of their professional identity development. Both partners engaged in it and expanded their professional identity by incorporating attributes of their partner’s. Building on these findings, we develop a model of professional identity co-construction in secure-base relationships that breaks new theoretical ground by exploring interpersonal identity relationships and highlighting their roots in the secure-base structure of a dyadic relationship.